Praktek Materi Fiqih Sebagai Bekal Mengajar Bagi Mahasiswa Jurusan PAI: Penelitian - Habibah, Alif Rohmah Nur (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is motivated by the importance of mastering Fiqh materials for students of the Islamic Religious Education (PAI) department as future educators. The main focus of this study is to equip students with practical skills, specifically in the procedures for caring for the deceased (tajhiz al-janazah) and the marriage contract (aqad nikah) process, to minimize religious practice errors in society. The implementation method was carried out through Community Service (PKM) activities involving stages of planning, socialization, theoretical delivery, direct practice (demonstration), simulation/role play, and evaluation. The results showed a significant increase in student competence. Evaluation data indicated that the ability to practice the funeral prayer increased from 40% to 85%, while the ability to practice the marriage contract increased from 45% to 88%. It is concluded that integrating theoretical material with direct practice is effective in improving pedagogical competence, self-confidence, and the readiness of PAI students to teach Fiqh materials applicably in the field.